Coagulation of Blood Plasma of Guinea Pig by the Bone Matrix - Huggins, Charles B. (1973)
Optimal amounts of demineralized bone matrix possess the ability to coagulate platelet-free heparinized, citrated, and oxalated blood plasmas of guinea pigs. Clotting constituents become denatured in contact with the insoluble coagulant proteins. Quantities in excess of optimal modify plasma so that it does not gel when thrombin is added. The newly described coagulant effects are not restricted to the bone matrix, but are present also in the demineralized matrices of tooth and ivory, and in denatured tendon as well. They are regulated properties that were not demonstrated in mineralized bone or native tendon. The coagulant attributes of bone matrix are consistent with those of electropositive polymers of a specific sort.